The Influence of ROE and DER to Stock Price Automotive and Components Companies Listed on Indonesian Stock Exchange Between 2010 – 2020 - Putri Amalia; Sutiman Sutiman; Ahmad Nazir (Indonesian Financial Review, 2022)
This study aims to examine the effect of Return On Equity (ROE) and Debt to Equity Ratio (DER) on Stock Prices in Automotive and Component Companies listed on the IDX for the 2010-2020 period, this analysis uses 2 (two) independent variables, namely Return On Equity ( ROE) and Debt to Equity Ratio (DER) and 1 (one) dependent variable, namely Stock Price. This research uses data panel. The results are that the best model of this research is random effect. ROE has not a significant effect but DER has a significant effect and negative partially. ROE and DER have a significant effect on Stock Prices simultaneously.